The ideal percentage of K substitution by Na in Eucalyptus seedlings Evidences from leaf carbon isotopic composition, leaf gas exchanges and plant growth - de Souza Mateus, Nikolas (Plant physiology and biochemistry : PPB, 2019)
Copyright © 2019 Elsevier Masson SAS. All rights reserved.